2022
DOI: 10.1021/acsenergylett.2c00763
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls and Protocols: Evaluating Catalysts for CO2 Reduction in Electrolyzers Based on Gas Diffusion Electrodes

Abstract: The evaluation of catalysts on gas diffusion electrodes (GDEs) have propelled the progress of electrochemical CO 2 reduction reaction (CO 2 RR) at industry-relevant activities. However, high experimental complexities exist in GDE-based flow electrolyzers, whereby various experimental factors can influence the evaluation of catalytic CO 2 RR performances. Not accounting for these experimental factors could result in inconsistent conclusions and thus hinder rational catalyst developments. This Perspective highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 88 publications
(215 reference statements)
0
14
0
1
Order By: Relevance
“…Thus far, the intrinsic activity of different electrocatalysts in a particular electrolyte varies significantly in literature. [147][148][149] The major contributor to this discrepancy is the inaccurate calculation of cathodic voltage, FE and catalyst deposition. This discrepancy in the literature data is mainly because of the different types of GDE cells used by different groups and the protocols followed during CO 2 RR operation.…”
Section: Benchmarking Catalyst Evaluation In Gdementioning
confidence: 99%
“…Thus far, the intrinsic activity of different electrocatalysts in a particular electrolyte varies significantly in literature. [147][148][149] The major contributor to this discrepancy is the inaccurate calculation of cathodic voltage, FE and catalyst deposition. This discrepancy in the literature data is mainly because of the different types of GDE cells used by different groups and the protocols followed during CO 2 RR operation.…”
Section: Benchmarking Catalyst Evaluation In Gdementioning
confidence: 99%
“…3,[11][12][13][14] In recent CO 2 RR studies, gas-diffusion type flow electrolyzers were widely employed to deliver industrially relevant reaction rate and selectivity by improving the mass transport of CO 2 from the gas phase to the catalyst surface. 5,[15][16][17] CO 2 RR performance with over 60% faradaic efficiency of C 2+ products at current densities 4100 mA cm À2 has been achieved in numerous recent reports. [18][19][20][21][22][23] Owing to the structural complexity of the gas-diffusion electrode (GDE) and varied configurations of flow electrolyzers employed in the literature, it is unclear whether the reported CO 2 RR performance reflects the intrinsic activity of the catalysts, as it is commonly assumed, or features of flow reactors.…”
mentioning
confidence: 94%
“…[18][19][20][21][22][23] Owing to the structural complexity of the gas-diffusion electrode (GDE) and varied configurations of flow electrolyzers employed in the literature, it is unclear whether the reported CO 2 RR performance reflects the intrinsic activity of the catalysts, as it is commonly assumed, or features of flow reactors. 5,15,24,25 In this work, we evaluated the CO 2 RR performance of three commercial Cu catalysts, i.e., nanoparticle Cu (NP Cu, purchased from Sigma-Aldrich), spherical Cu (Sph Cu, purchased from Macklin), and copper oxide (CuO, purchased from Alfa Aesar), using a gas-diffusion type microfluidic flow electrolyzer that has been widely employed in CO 2 electrolysis. We showed that all three commercial catalysts were able to deliver FE of C 2+ products above 70% at 200 mA cm À2 , and notably, NP Cu could achieve near 80% FE of C 2+ products at 300 mA cm À2 .…”
mentioning
confidence: 99%
See 2 more Smart Citations